Identification of animal hosts of Fort Sherman virus, a New World zoonotic orthobunyavirus. Issue 4 (16th February 2020) - de Oliveira Filho, Edmilson F.; Carneiro, Ianei O.; Ribas, Jorge R. L.; Fischer, Carlo; Marklewitz, Marco; Junglen, Sandra; Netto, Eduardo Martins; Franke, Carlos Roberto; Drexler, Jan Felix
Abstract: An orthobunyavirus termed Fort Sherman virus (FSV) was isolated in 1985 from a febrile US soldier in Panama, yet potential animal reservoirs remained unknown. We investigated sera from 192 clinically healthy peri‐domestic animals sampled in northeastern Brazil during 2014–2018 by broadly reactive RT‐PCR for orthobunyavirus RNA, including 50 cattle, 57 sheep, 35 goats and 50 horses. One horse sampled in 2018 was positive (0.5%; 95% CI, 0.01–3.2) at 6.2 × 10 3 viral RNA copies/mL. Genomic comparisons following virus isolation in Vero cells and deep sequencing revealed high identity of translated amino acid sequences between the new orthobunyavirus and the Panamanian FSV prototype (genes: L, 98.8%; M, 83.5%; S, 100%), suggesting these viruses are conspecific. Database comparisons revealed even higher genomic identity between the Brazilian FSV and taxonomically unassigned Argentinian mosquito‐ and horse‐derived viruses sampled in 1965, 1982 and 2013 with only 1.1% maximum translated amino acid distances across viral genes, suggesting the Argentinian viruses were also distinct FSV strains. The Panamanian FSV strain was an M gene reassortant relative to all Southern American FSV strains, clustering phylogenetically with Cache Valley virus (CVV). Mean dN/dS ratios among FSV genes ranged from 0.03 to 0.07, compatible with strong purifying selection. FSV‐specific neutralizing antibodies occurred at relatively high end‐point titres in the range of 1:300 in 22.0% of horses (11 out of 50 animals), 8.0% of cattle (4/50 animals), 7.0% of sheep (4/57 animals) and 2.9% of goats (1/35 animals). High specificity of serologic testing was suggested by significantly higher overall FSV‐specific compared to CVV‐ and Bunyamwera virus‐specific end‐point titres ( p  = .009), corroborating a broad vertebrate host range within peri‐domestic animals. Growth kinetics using mosquito‐, midge‐ and sandfly‐derived cell lines suggested Aedes mosquitos as potential vectors. Our findings highlight the occurrence of FSV across a geographic range exceeding 7, 000 km, surprising genomic conservation across a time span exceeding 50 years, M gene‐based reassortment events, and the existence of multiple animal hosts of FSV.